The association between vision impairment and multi-site pain in middle-aged and older adults in China: results from the China health and retirement longitudinal study - Tianyi Luo; Cunzi Li; Lan Zhou; Lan Zhou; Yingrui Liu; Hongyan Sun; Ming Ming Yang (Frontiers in Public Health)
BackgroundPrevious research on the association between vision impairment (VI) and multi-site pain has been sparse, and no studies have specifically examined this relationship in low- and middle-income countries (LMICs).ObjectiveThis study aims to investigate the relationship between VI and the coexistence of pain in 15 different body sites and multi-site pain among middle-aged and older adults in China using nationally representative survey data.MethodsWe conducted a cross-sectional study using data from the 2020 China Health and Retirement Longitudinal Study (CHARLS), which included 10,240 participants. We used the Mann–Whitney U test and chi-square test to compare the sociodemographic, economic, and health status characteristics of the participants. Two logistic regression models were constructed to analyze the relationship between VI and the coexistence of pain in different body sites and multi-site pain.ResultsParticipants with VI had a higher probability of experiencing pain across 15 body sites compared to those without VI. After adjusting for sociodemographic, economic, and health status factors, pain in eight different body sites was significantly associated with VI (p < 0.05). The most significant associations were observed for waist pain (p = 0.003), finger pain (p = 0.012), and knee pain (p = 0.009). Furthermore, VI was inversely associated with the coexistence of pain in two body sites (OR: 0.547; 95% CI: 0.354–0.810, p < 0.05) but positively associated with five or more body sites (OR: 1.550; 95% CI: 1.191–2.017, p < 0.05). Sensitivity analysis revealed that VI remained positively associated with the coexistence of five or more painful body sites after stratifying by age, gender, and place of residence (p < 0.05).ConclusionOur study revealed that Chinese middle-aged and older individuals with VI tended to experience multi-site pain, exhibiting a negative correlation with two coexisting painful sites and a positive correlation with five or more. The association between VI with the coexistence of five or more painful body sites was not influenced by age, gender, or place of residence. These findings suggest that in LMICs, VI often occurs with multi-site pain, and patients with pain could benefit from ophthalmic care and vision rehabilitation. This has major implications for improving healthcare efficiency, service planning, and clinical practice. However, VI was assessed in this study through interviewer observation rather than clinical examinations, which may have introduced misclassification bias, and future studies should validate these associations using objective visual assessments.